Upconversion luminescence and temperature sensing characteristics of Ho3+/Yb3+ co-doped tellurite glasses - (:unkn) unknown (ELSEVIER, 2021)
The upconversion emission spectra of Yb3+/Ho3+ co-doped TeO2-ZnO-BaO glasses were studied for solid-state lighting and optical thermometry. The studied glasses were prepared using the melt quenching technique. The green and red UC emissions of Ho3+ ions are due to two-photon absorptions, which cause the various energy transfer processes. The studied glasses show tunable color properties and high-temperature sensor sensitivity. Color coordinates on the CIE chromaticity diagram of those were affected by the pump power and shifted from green to red region at higher Ho3+ concentrations. The F-5(5) level and (F-3(4), S-5(2)) levels of Ho3+ are found to be thermally coupled levels. The energy difference (Delta E) between these levels is calculated as 2463.66 cm(-1). Among the studied glasses, Yb3+(3.0 mol%)/Ho3+(0.15 mol %) co-doped TeO2-ZnO-BaO show the highest absolute sensitivity of 0.011K(-1) at 503K. In the light of conducted observations, the studied glasses are proposed as a good candidate material for lighting and optical temperature sensing.
Keywords: Telluride glasses; Upconversion; Optical thermometry; Color tunability; THERMOMETRY; HO3+; PHOTOLUMINESCENCE; DEPENDENCE